On crystallographic aspects of heterogeneous plastic flow during ductile tearing: 3D measurements and crystal plasticity simulations for AA7075-T651. (September 2021) - Morgeneyer, Thilo F.; Khadyko, Mikhail; Buljac, Ante; Helfen, Lukas; Hild, François; Benallal, Ahmed; Børvik, Tore; Hopperstad, Odd S.
Abstract: Crystallographic aspects of heterogeneous plastic flow during ductile tearing are assessed experimentally by combining in situ synchrotron laminography imaging of notched flat samples with a full-field measurement technique and numerical simulations with the crystal plasticity finite element method (CP-FEM). Advantage is taken of the plane strain condition in the region ahead of the notch root ( i.e., in the plane normal to the crack propagation direction) to perform two-dimensional image correlation in the material bulk. Intermetallic particles provide image contrast that is registered during the correlation analyses. They reveal the early onset of slant strained bands along which the final slant crack propagated. Two-dimensional plane strain CP-FEM simulations using the grain shape and crystallographic orientations of the studied material show the same trends as those observed experimentally, namely, the appearance of early slant strained bands that cross tens of grains and that remain stable over the loading history. The ratio of the strains within and outside the bands is also similar to that observed experimentally. Highlights: In situ ductile tearing of an AA7075 T651 alloy was performed by 3D laminography. Image correlation techniques allowed strain to be measured inside the material. Early slant strained bands were found crossing tens of grains through the thickness. CPFEM simulations using the real grain shape and orientation were performed. The simulations captured the experimentally found slant strained bands.